Bifunctional oxidative and acidic titanium silicalite (TS-1) catalysts for one pot synthesis of 1,2-octanediol from 1-octene - Prasetyoko, Didik (2006)
New bifunctional catalysts containing both oxidative and Brønsted acidic sites have been prepared and used for the consecutive transformation of alkenes to the corresponding diols via the formation of epoxides with aqueous hydrogen peroxide as oxidant. The catalytic system was designed in order such that two kinds of active sites would allow for the epoxidation of alkenes to take place within the pore channels of titanium-containing molecular sieve while acid catalysis of the epoxides to diols occurs on the external surface of the catalyst. Based on this design, titanium silicalite (TS-1), an excellent and commercial oxidation catalyst known so far, has been chosen. The TS-1 was then modified with different acidic oxide precursors. Synthesis of the series of bifunctional catalysts was achieved by deposition of various loadings of acidic oxide precursors up to 25 wt% onto TS-1 powder. The Ti4+ and acidic oxides in the TS-1 molecular sieve served as oxidative and acidic sites, respectively. The thus obtained bifunctional catalysts were sulfated TS-1 (SO4 2-/TS-1), sulfated titanium oxide supported on TS-1 (SO4 2-Ti/TS-1), tungsten oxide supported on TS-1 (WO3/TS-1), sulfated zirconia supported on TS-1 (SZ/TS-1), and niobium oxide supported on TS-1 (Nb/TS-1). The X-ray diffraction analysis revealed that TS-1 still retained the MFI structure after incorporation of the acidic oxides even when the crystallinity is lower. The infrared (IR) and ultra-violet diffuse reflectance (UV-Vis DR) spectra showed that the titanium in TS-1 was mainly in tetrahedral coordination after incorporation of acidic oxides. Results of pyridine adsorption followed by IR spectroscopy showed the presence of Brønsted acid sites in WO3/TS-1, Nb/TS-1 and highly loaded SZ/TS-1 but not sulfated samples of TS-1 (SO4 2-/TS-1 and SO4 2-Ti/TS-1). In the consecutive transformation of 1-octene to 1,2-octanediol through the formation of 1,2-epoxyoctane, all the catalysts showed a significant increase in the rate of formation of 1,2-epoxyoctane with respect to TS-1. The presence of acidic oxides in TS-1 was proposed to explain the increased hydrophilic character of the catalysts, which is responsible for the higher rate of formation of reactive oxo-titanium species. Moreover, the acid sites were shown to effectively catalyze the formation of 1,2-octanediol with the 10 wt% niobium oxide supported on TS-1 giving the highest yield. Comparison of the catalytic performance of the prepared bifunctional catalysts with that of the mechanical mixture comprising of TS-1 and H-ZSM-5 (Brønsted acid), showed that the bifunctional catalysts were more active; suggesting that specific location of the two active sites plays an important role in the consecutive transformation of alkenes to epoxides and then diols. The higher activity of the bifunctional catalysts was supposedly due to the location of the acidic sites in the immediate vicinity of the oxidative sites which enabled the epoxidation products to undergo hydrolysis rapidly at the Brønsted acid sites that were located on the external surface of TS-1